Taking Variation Seriously: Testing the Steatite Mast-Processing Hypothesis with Microbotanical Data from the Hunter's Home Site, New York - J. P. Hart; Reber, E. A.; Thompson, R. G.; Lusteck, R. (American Antiquity, 2008)
In a series of recent publications, Truncer (2004a, 2004b, 2006) presents a hypothesis that during what he interprets as the peak period of use (cal. 2500--1500 B.C.) in eastern North America, steatite (soapstone) vessels were specialized cooking tools used to process mast. A key component of Truncer’s hypothesis building is his interpretation of an analysis of fatty acids extracted from charred residue adhering to four steatite sherds, which he interpreted to be consistent with mast. This is the only component of his hypothesis building that directly links steatite vessel use to mast processing. Here we convey the results of a reassessment of Truncer’s analytical results and the results of our own analysis of phytoliths and fatty acids extracted from charred residue adhering to three sherds from the Hunter’s Home site. Our results undermine this key component of Truncer’s hypothesis building and therefore the hypothesis itself.
Keywords: acorns; cooking residue analysis; cooking vessels; lipids; phytoliths; soapstone; Steatite